Adapting a yam seed technique to meet farmers’ criteria - Odu, B.O.; Coyne, Danny L.; Kumar, P. Lava (2016)
Seed yam is costly, and can carry pests and diseases. To reduce costs and to manage seed health, in the 1970s, the Yam Minisett Technique (YMT) was developed, which involved cutting yams into small pieces to be used as seed. Few farmers adopted the technique, in part because of the high labor requirements of making a nursery to sprout the pieces of tuber. In 1992, a DFID-funded project introduced fungicide and insecticide treatment to improve the survival of yam minisetts. The Adapted Yam Minisett Technique (AYMT) was developed during 2003 to 2006 in response to the technical problems of the YMT. The AYMT involved larger pieces of yam, dipped in a solution of fungicide and insecticide, to help manage pests and to ensure that more of the pieces survived. This allowed farmers to skip making the tedious seedbed, and to plant directly in the field. The technique was adapted on four on-farm trials. About 400 farmers in Kogi State, Nigeria have tried the technique. They had credit to buy the pesticides. Although various subsequent projects have promoted the AYMT, farmer response to the technique is yet to be quantified.